Using Repeated Reading to Improve Reading Speed and Comprehension in Students with Visual Impairments. (March 2013) - Savaiano, Mackenzie E.; Hatton, Deborah D.
Introduction: This study evaluated whether children with visual impairments who receive repeated reading instruction exhibit an increase in their oral reading rate and comprehension and a decrease in oral reading error rates. Methods: A single-subject, changing-criterion design replicated across three participants was used to demonstrate the association between a repeated reading intervention and the oral reading rate, comprehension, and error rate. Results: Visual analysis of the data indicates that there was a functional relation between repeated reading and oral reading rate for two participants, and a functional relation between repeated reading and comprehension for all participants. There was not a functional relation between repeated oral reading and error rate. Discussion: Based on the results of this study, repeated reading appears to be an effective practice for some students with visual impairments. Implications for practitioners: Teachers and parents can engage children in repeated reading activities in an effort to develop automaticity in reading and to improve oral reading rates.